Efficient and selective hydrogen peroxide-mediated oxidation of sulfides in batch and segmented and continuous flow using a peroxometalate-based polymer immobilised ionic liquid phase catalyst. Issue 3 (18th December 2014) - Doherty, S.; Knight, J. G.; Carroll, M. A.; Ellison, J. R.; Hobson, S. J.; Stevens, S.; Hardacre, C.; Goodrich, P.
Abstract : Highly efficient sulfide oxidation has been achieved under segmented and continuous flow using a peroxometalate-based polymer immobilised ionic liquid phase catalyst. Abstract : The peroxometalate-based polymer immobilized ionic liquid phase catalyst [PO4 {WO(O2 )2 }4 ]@PIILP has been prepared by anion exchange of ring opening metathesis-derived pyrrolidinium-decorated norbornene/cyclooctene copolymer and shown to be a remarkably efficient system for the selective oxidation of sulfides under mild conditions. A cartridge packed with a mixture of [PO4 {WO(O2 )2 }4 ]@PIILP and silica operated as a segmented or continuous flow process and gave good conversions and high selectivity for either sulfoxide (92% in methanol at 96% conversion for a residence time of 4 min) or sulfone (96% in acetonitrile at 96% conversion for a residence time of 15 min). The immobilized catalyst remained active for 8 h under continuous flow operation with a stable activity/selectivity profile that allowed 6.5 g of reactant to be processed (TON = 46 428) while a single catalyst cartridge could be used for the consecutive oxidation of multiple substrates giving activity-selectivity profiles that matched those obtained with fresh catalyst.